2004
DOI: 10.1111/j.1440-1827.2004.01647.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemically detectable Cdx2 is present in intestinal phenotypic elements in early gastric cancers of both differentiated and undifferentiated types, with no correlation to non‐neoplastic surrounding mucosa

Abstract: It has previously been reported that Cdx2 is the useful prognostic and intestinal phenotypic marker in advanced gastric cancers (GC). In this study, Cdx2 expression and phenotype in early GC and non-neoplastic surrounding mucosa were examined. A total of 130 early GC (70 intramucosal and 60 submucosally invasive cancers) histologically and phenotypically were evaluated. The expression of Cdx2 was assessed by immunohistochemistry. The lesions were phenotypically divided into 44 gastric (G), 42 gastric and intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(85 citation statements)
references
References 38 publications
4
80
1
Order By: Relevance
“…Previous reports have shown the rates of the G, GI, I, and N types of early undifferentiated-type adenocarcinoma, including signet-ring cell carcinoma, to be 27.8-62.4 %, 24.7-68.5 %, 0-23.1 %, and 0-10.8 %, respectively [9,10,13,14,17,26]. In contrast to the above findings based on MUC only, PURE-type carcinomas in the present study were classified into 17.9 % (19/106) G type, 78.3 % (83/ 106) GI type, 1.9 % (2/106) I type, and 1.9 % (2/106) N type based on MUC and CDX2.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous reports have shown the rates of the G, GI, I, and N types of early undifferentiated-type adenocarcinoma, including signet-ring cell carcinoma, to be 27.8-62.4 %, 24.7-68.5 %, 0-23.1 %, and 0-10.8 %, respectively [9,10,13,14,17,26]. In contrast to the above findings based on MUC only, PURE-type carcinomas in the present study were classified into 17.9 % (19/106) G type, 78.3 % (83/ 106) GI type, 1.9 % (2/106) I type, and 1.9 % (2/106) N type based on MUC and CDX2.…”
Section: Discussionmentioning
confidence: 98%
“…The positivity rate was higher for CDX2 than for MUC2, and CDX2 expression was detected in cancerous areas not only where MUC2 expression was apparent, but also in tissues exhibiting only gastric markers or null phenotypic lesions. Previous reports have shown that there is a positive correlation between CDX2 expression and MUC2 [21,33], and that CDX2 expression might precede intestinal phenotypic expression during a shift from gastric to intestinal phenotype with the progression of gastric carcinomas [17]. Thus, CDX2 appears to be a more sensitive marker than MUC2 for assessing the presence of intestinal phenotypic expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations